Assessment of SADC Countries' National Adaptation Planning Health Impacts Inclusion: A Thorough Review - Renate Meyer; Caradee Wright; Hanna-Andrea Rother (Ubiquity Press, 2024)
Background: The impacts of climate change are recognised as a key challenge of the 21st century. By 2030, Sub-Saharan Africa is projected to have the globally highest burden of disease due to climate change. Objectives: This study aims to evaluate the strengths and weaknesses of the National Adaptation Plans (NAPs) of the Southern African Development Community (SADC), a sub-region under-represented at a global level, in addressing current and future climate change-related health impacts. It specifically assesses the NAPs of Botswana, Mozambique, Namibia, South Africa, and Zimbabwe. Methods: A thorough review was conducted, analysing articles, government reports, and national communications related to NAPs and climate change health outcomes in the selected countries. Sources were evaluated against pre-defined inclusion and exclusion criteria. Main findings: All five countries prioritised health in their NAPs; however, health departments were excluded from assessments in two of the countries. Although health surveillance and early warning systems were included in the NAPs, there was limited evidence of their integration into broader climate, health, economic, and labour policies. National climate change focal points were identified, but governance and implementation at district and local levels were not well-documented. This review highlighted a need for greater inclusion of Indigenous and locally led knowledge. Common barriers identified included the lack of data with appropriate frequency and scale. Governance and implementation difficulties were also identified in all five countries; these difficulties included both a lack of coordination and a lack of institutional capacity. These challenges, especially a lack of political will to address the compound impacts of altered climate and health on all earth systems, are also found at the regional level. Conclusions: National strategies and implementation programs in SADC countries need to be agile in their ability to scale and adapt, yet they also need to include measurable actions and timeframes. Given the shared climate and health trends and the interconnected socio-economic, environmental, and political landscape, there is significant potential for regional coordination to address cross-border climate change impacts and to optimise resource use.